Comparison of the Value of Neutrophil to High-Density Lipoprotein Cholesterol Ratio and Lymphocyte to High-Density Lipoprotein Cholesterol Ratio for Predicting Metabolic Syndrome Among a Population in the Southern Coast of China - Chen T (Dove Medical Press, 2020)
Tong Chen, Haishan Chen, Hua Xiao, Hongjuan Tang, Zhicong Xiang, Xin Wang, Xuan Wang, Hequn Zou Department of Nephrology, The Third Affiliated Hospital, Southern Medical University, Guangzhou 510630, People’s Republic of ChinaCorrespondence: Hequn ZouDepartment of Nephrology, The Third Affiliated Hospital, Southern Medical University, Guangzhou 510630, People’s Republic of ChinaEmail Hequnzou@hotmail.comBackground: This study aimed to determine the optimal cutoff values and evaluate the associations of neutrophil to high-density lipoprotein cholesterol ratio (NHR) and lymphocyte to high-density lipoprotein cholesterol ratio (LHR) with metabolic syndrome (MetS), stratified by sex.Methods: A large-scale cross-sectional survey was conducted among 1401 adults from January to April 2018 in six communities in Wanzhai Town, Zhuhai City, on the southern coast of China. Receiver operating characteristics (ROC) analyses and logistic regression analysis were conducted to assess the optimal cutoff and value of NHR and LHR for predicting MetS.Results: Hematological parameters showed the correlation with the occurrence of MetS (red blood cells, hemoglobin, and white blood cells and subtypes). Binomial logistic regression analysis found that LHR (OR:  3.671; 95% CI: 2.385– 5.651; p< 0.001) and NHR (OR: 1.728; 95% CI: 1.353– 2.207; p< 0.001) can predict MetS in females, independent of confounding factors. Although LHR (OR: 1.571; 95% CI: 1.001– 2.468; p=0.05) and NHR (OR: 1.163; 95% CI: 0.909– 1.48; p< 0.01) were independent risk factors for MetS in males after adjustment for age, current smoking, current alcohol use, physical activity,  educational attainment, waist circumference, systolic pressure, diastolic pressure and hypersensitive C-reactive protein (hs-CRP), when further adjusted for fasting plasma glucose level, LHR and NHR, both lost their independence. ROC curves showed that LHR had the highest AUC for predicting MetS in females and NHR had the highest AUC in males. The cutoff points of LHR and NHR were 1.36 and 2.31 in females, and  1.96 and 3.38 in males.Conclusion: LHR and NHR may become valuable makers and have strong predictive power for predicting MetS, especially in females.Keywords: neutrophil to high-density lipoprotein cholesterol ratio, lymphocyte to high-density lipoprotein cholesterol ratio, metabolic syndrome